Novel Eudragit® -based polymeric nanoparticles for sustained release of simvastatin - Deborah Fernandes Rodrigues; Renê Oliveira do Couto; Rubén Dario Sinisterra; Carlos Eduardo de Matos Jensen (Universidade de São Paulo, 2020)
This paper reports on the development of nanoparticles aiming at the in vitro controlled release of simvastatin (SVT). The nanoparticles were prepared by the nanoprecipitation method with polymers Eudragit® FS30D (EDGFS) or Eudragit® NE30D (EDGNE). EDGFS+SVT nanoparticles showed mean size of 148.8 nm and entrapment efficiency of 76.4%, whereas EDGNE+SVT nanoparticles showed mean size of 105.0 nm and entrapment efficiency of 103.2%. Infrared absorption spectra demonstrated that SVT incorporated into the polymer matrix, especially EDGNE. Similarly, the differential scanning calorimeter (DSC) curve presented no endothermic peak of fusion, indicating that the system is amorphous and the drug is not in the crystalline state. The maintenance of SVT in the amorphous state may favors its solubilization in the target release sites. In the in vitro dissolution assay, the SVT incorporated into the EDGFS+SVT nanoparticles showed a rapid initial release, which may be related to the pH of the dissolution medium used. Regarding the EDGNE+SVT nanoparticles, the in vitro release occurred in a bimodal behavior, i.e., an initial "burst" followed by a sustained delivery, with the kinetics of drug release following Baker-Lonsdale's mathematical model. All these features suggest the nanoparticulate system's potential to modulate SVT delivery and enhance its bioavailability.